Pengaruh Financial Leverage, Kualitas Audit Dan Pertumbuhan Perusahaan Terhadap Manajemen Laba - Febria Hanisa; Elvi Rahmi (Universitas Negeri Padang, 2021)
The purpose of this study was to determine the effect of financial leverage, audit quality and corporate growth simultaneously and partially on earnings management in non-financial service companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia: BEI) in 2016-2018. This type of research is causative. The subjects and objects in this research are non-financial service companies listed on the IDX during 2016 to 2018, amounting to 298 companies. This research uses purposive sampling technique and 93 companies were used as the sample technique. The Data collection techniques uses documentation techniques. Method is used regression analysis. Based on the results found simultaneously significant test (together) there is a significant influence between the variables of financial leverage, audit quality and company growth on earnings management. Partially significant test result show that financial leverage has no significant effect on earnings management, audit quality has a significant management and company growth has a significant effect on management. Regarding management, it is expected that investors and the public will be more careful in reading information in financial statements so that later there are no mistaken in making a decision to invest..Keywords : financial leverage, audit, growth, earning management